IMPROVEMENT OF RENT RELATIONS AS A FACTOR OF INCREASING THEENERGY EFFICIENCY OF UKRAINIAN ECONOMY - А. Grazhevska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article addresses prerequisites and consequences of counterproductive rent-seeking behavior of economic agents as a factor that contributes to the low energy efficiency of the national economy.Author justifies the necessity and strategic directions of improvement of state regulation of rent relations in order to modernize the economy of Ukraine.